Chemical properties of Acacia Mangium - Nasarudin, Nurul Fatihah; Mokhtar, Norain (2010)
The research was carried out to study the chemical properties of Acacia Mangium in mature tree. Chemical component of wood influence the characteristics, properties and opportunities for use of natural composite. The main objective of the study was to determine basic chemical component of Acacia Mangium from mature tree and the effect of tree portion, namely, top, middle, and bottom also studied. Acacia Mangium wood was analysed for cold-water, hot- water, ash content, lignin, alcohol- benzene, 1 % NaOH solubility and Holocellulose but the experiments that have been completed were Moisture Content. With this experiment, the different properties percentages of amount within the acacia mangium such as tannins, gums, sugars, starch, coloring matter, content of lignin and ash could be determine.